2019
DOI: 10.3390/jcm8010116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NADPH Oxidase 4 (NOX4) Signaling Attenuates Tuberculous Pleural Fibrosis

Abstract: Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase [NOX] enzymes serve several hemostatic and host defense functions in various lung diseases, but the role of NOX4 signaling in tuberculous pleurisy is not well understood. The role of NOX4 signaling in tuberculous pleural fibrosis was studied using invitro pleural mesothelial cell (PMC) experiments and a murine model of Mycobacterium bovis bacillus Calmette–Guérin (BCG) pleural infection. The production of NOX4 reactive oxygen species (NOX4–ROS) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…NOX4 is upregulated in fibrosis, and its genetic or pharmacological inhibition decreases ECM deposition and TGF-β1-dependent fibrosis-promoting response significantly. 38,39 Our result suggested that Tan IIA reduced the upregulated mRNA and protein levels of NOX4 in silicosis rats. Thus, the antifibrotic effect of Tan IIA may also be attributed to NOX4 inhibition induced decrease in oxidative stress.…”
Section: Discussionmentioning
confidence: 56%
“…NOX4 is upregulated in fibrosis, and its genetic or pharmacological inhibition decreases ECM deposition and TGF-β1-dependent fibrosis-promoting response significantly. 38,39 Our result suggested that Tan IIA reduced the upregulated mRNA and protein levels of NOX4 in silicosis rats. Thus, the antifibrotic effect of Tan IIA may also be attributed to NOX4 inhibition induced decrease in oxidative stress.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies have reported the interrelation between TLR4 and NOXs. Wang et al elaborated that TLR4 blocking reduced salt-induced prehypertension response via NADPH oxidases [28], while a study from Kim et al also suggested a regulation effect of NOX4 on TLR4 [29]. We wondered the directional regulation; hence, siRNA against TLR4 or NOX2 were used prior to OSS exposure in ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the Nox family, NOX4is upregulated in several pulmonary diseases including tuberculous brosis, idiopathic pulmonary brosis, and lung cancer [26,27]. Ling et al, reported signi cantly higher NOX4 levels in a rat model of ventilator-induced lung injury [28].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 184 patients were enrolled; of these, only97patients were successfully extubatedwithin3 weeks. Patients with extubation failure were signi cantly older (76 vs.69years, P = 0.003).The APACHE II score and SOFA score in the failed extubation group were signi cantly higher than that in the successful extubation group [median (IQR), APACHE:23 (20)(21)(22)(23)(24)(25)(26)(27)(28) vs. 19 (15)(16)(17)(18)(19)(20)(21)(22)(23); P<0.001, SOFA: 9 (7-12) vs 6 (5-9); P<0.001];however, no signi cant between-group difference was observed with respect to Charlson comorbidity index [2(1, 3) vs. 2 (1, 3), P = 0.225].The indications for intubation and the proportion of patients with pneumonia at admission were not different between the two groups.…”
Section: Characteristics Ofthe Study Populationmentioning
confidence: 99%